ANALISIS PENGGUNAAN MEDIA LAGU DALAM MENINGKATKAN MINAT BELAJAR DAN DAYA INGAT SISWA SEKOLAH DASAR - Pramesti, Erlintang; Khofifah, Ayu Dewi Nafisatul; Shallum, Geitsya Alodia; Wijayanto, Wasis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of song media in increasing learning interest and memory of elementary school students, especially in grades III and IV. The background of this study is based on the problem of low student learning interest caused by monotonous teaching methods and the minimal use of interesting learning media. This study uses a descriptive qualitative approach with data collection techniques in the form of observation and documentation, which is strengthened by a literature review from various relevant scientific sources. Data are analyzed through the stages of data reduction, information presentation, and conclusion drawing. The results of the study indicate that the use of song media, such as the song "Adiksimba" in the material of question sentences in grade III and the song "Pelangi Paragraf" in the material of types of paragraphs in grade IV, is able to increase enthusiasm, active participation, and student memory of the material taught. The elements of melody, rhythm, and lyrics in the song are proven to form a strong memory pattern so that learning information is easier for students to understand and remember. Thus, song media can be used as an alternative effective Indonesian language learning media to increase learning interest and memory of students at the elementary school level.